ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN SEPEDA MOTOR DI KOTA SEMARANG (Studi Kasus : PNS Kota Semarang) - Budiarto, Arief; Purwanti, Evi Yulia (Diponegoro Journal of Economics, 2013)
Semarang city is the center of government, commerce, education and others in Central Java. High mobility makes transportation system is very important, both the transport of goods and people. Current urban transport problems have become a very complex issue, especially because of the increasing dependence of the city on private vehicles both cars and motorcycles. As a result, the number of vehicles that is not accommodated by the condition of the road is available. This causes congestion becomes higher and seemed to be accepted as has been customary for the city, including Semarang. The purpose of this study was to analyze the factors that influence the demand for motorcycles in the city of Semarang. The variables used in this study is income, public transport tariff, number of family members, motorcycle prices, and tastes. Types of data collected primary data from Surveying using questionnaires completed by respondents are civil servants (PNS) in Semarang and secondary data from the literature-literature related to this study. Based on the results of the regression analysis motorcycle demand in the city of Semarang at 61.63% can be explained by the variable income, public transport tariff, number of family members, motorcycle prices, and tastes. Revenue has positive and significant impact on demand for motorcycles, public transportation tariff has positive and significant, number of family members have a positive and significant impact on demand for motorcycles, motorcycle prices and no significant negative effect on demand for motorcycles and taste negatively affect the demand for bicycles motors.